2010
DOI: 10.1007/s11664-010-1382-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Sn-3.5Ag-Based Solders Containing Zn and Al Additions on Cu and Ni(P) Substrates

Abstract: In this study we consider the effect of separately adding 0.5 wt.% to 1.5 wt.% Zn or 0.5 wt.% to 2 wt.% Al to the eutectic Sn-3.5Ag lead-free solder alloy to limit intermetallic compound (IMC) growth between a limited volume of solder and the contact metallization. The resultant solder joint microstructure after reflow and high-temperature storage at 150°C for up to 1000 h was investigated. Experimental results confirmed that the addition of 1.0 wt.% to 1.5 wt.% Zn leads to the formation of Cu-Zn on the Cu sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…In addition to causing δ-Cu33Al17 to form, Al additions reduced the nucleation undercooling from 46.3 to 3.6 K (see Table 1), similar to past work [1][2][3]. With an undercooling of only ~4K, only a very slightly hypoeutectic alloy would form primary Cu6Sn5 and it is not surprising that primary Cu6Sn5 does not form in Sn-0.7Cu-0.05Al freestanding balls.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…In addition to causing δ-Cu33Al17 to form, Al additions reduced the nucleation undercooling from 46.3 to 3.6 K (see Table 1), similar to past work [1][2][3]. With an undercooling of only ~4K, only a very slightly hypoeutectic alloy would form primary Cu6Sn5 and it is not surprising that primary Cu6Sn5 does not form in Sn-0.7Cu-0.05Al freestanding balls.…”
Section: Methodssupporting
confidence: 81%
“…Potential benefits of dilute Al additions include (i) the suppression of nucleation undercooling for βSn in Sn-Ag-Cu [1,2] and Sn-Ag [3] solders, which has been linked to a reduction in primary (pro-eutectoid) Ag3Sn blade formation [4] and may have the potential to grain refine the βSn phase in solder joints [5]; (ii) the suppression of Cu6Sn5 layer growth on Cu substrates [6]; and (iii) the introduction of small, hard Cu-Al intermetallics that could be harnessed as a dispersion in the βSn matrix to improve the performance and reliability of solder joints [5].…”
Section: Introductionmentioning
confidence: 99%
“…This has found that the undercooling can be suppressed significantly by additions including: Zn [1-3, 11, 24-34], Al [2,24,30,[34][35][36], Co [2, 32-34, 37, 38], Mn [2,30,33,39], Pt [40], Ti [33,39,41], and Pd [40]. Of these, Co [38], Pt [40], and Pd [40] have been deduced to suppress undercooling by introducing heterogeneous nucleant particles of αCoSn3, PtSn4, and PdSn4, each of which has been shown to be a relatively good lattice match to βSn and to form a reproducible crystallographic orientation relationship [38,40].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of minor alloying elements for the suppression of interfacial IMC growth has been widely studied [10][11][12][13][14][15][16] . Kotadia et al studied the addition of 0.5-1.5 mass% Zn to SnAgCu solder 17) .…”
Section: Introductionmentioning
confidence: 99%